'Be You Never So Gaye': A Queer Everyman - Irvin, Matthew W. (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2024)
The late medieval play Everyman might seem to exclude queerness, but its religious challenge to secular temporality is the very place to find the queer body of the past. Using Giorgio Agamben’s concept of ‘messianic time’ and queer theoretical interventions by Michel Foucault, J. Halberstam, and José Esteban Muñoz, this paper argues that Everyman creates a time for friendship as a way of life. That time is a ‘gaye’ time; though the theology of the play may foreclose that time of fellowship and pleasure, the performance of the play produces a time outside the grip of theological order.